The genus Apterogyna Latreille, 1809 in Egypt, with three new species (Hymenoptera: Bradynobaenidae: Apterogyninae) - Soliman, Ahmed M.; Gadallah, Neveen S.; Al-Shahat, Ahmed M.; Pagliano, G. (Zootaxa, 2015)
The genus Apterogyna Latreille is reviewed from Egypt, based on specimens collected from Wadi Digla (Cairo), Saint Catherine (South Sinai) and those deposited in Egyptian and Italian insect collections as well as recorded data from the literature. Five Apterogyna species were previously recorded from Egypt: A. grandii Invrea, A. latreillei Klug, A. mickeli Giner Marí, A. mocsaryi André, and A. olivieri Latreille. Three new species Apterogyna flavicapillata Soliman & Gadallah sp. nov. (South Sinai), A. oshaibahi Soliman & Gadallah sp. nov. (Wadi Digla), and A. similis Soliman & Gadallah sp. nov. (Giza) are described and illustrated. An illustrated key of eight Egyptian species of Apterogyna is given.